Role of nursing in the prevention of female (Research, Society and Development, 2021)
Objective: This study seeks to understand the role of nursing in the prevention of femicide, which in Brazil is increasingly frequent. Methods: Integrative review based on the guiding question: What is the role of Nursing in preventing femicide?. Searches were carried out in the LILACS, BVS and SciELO databases, using the descriptors “Violence against women”, “Women's rights” and “Nursing Care”, through the Booleans AND and OR. Articles that were available in Portuguese and English, available in full and dated in the last ten years, were used as inclusion criteria, due to the scarcity of material that included the relationship between femicide and nursing care in women's health. After analysis, 16 publications were selected to compose the discussion and presentation of this review. Results: Based on the analysis of the material obtained in the searches of the databases, it was understood the need for nursing professionals to encourage women who are or have experienced violence to perform self-care and direct the service and assistance network to these victims, as a means of preventing femicide. The guidance of these professionals on social interaction is essential, aiming at balancing the mental health of these women. Conclusion: Despite being a topic of total relevance in public health today, it is necessary to broaden the debate on gender violence within health services, so that nursing professionals can understand the phenomenon and deal with the consequences of violence suffered, knowing that the care provided to these women is mostly performed by this professional class.